2002
DOI: 10.2172/15010320
|View full text |Cite
|
Sign up to set email alerts
|

Test Summary Report Vitrification Demonstration of an Optimized Hanford C-106/AY-102 Waste-Glass Formulation

Abstract: In order to further the goal of optimizing Hanford's HLW borosilicate flowsheet, a glass-formulation effort was launched to develop an advanced high-capacity waste form exhibiting acceptable leach and crystal-formation characteristics. A simulated C-106/AY-102 waste envelope inclusive of LAW pretreatment products was chosen as the subject of these nonradioactive optimization efforts. To evaluate this optimized borosilicate waste formulation under continuous dynamic vitrification conditions, a research-scale Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The crystallization of the magnetitic spinels is a common phenomenon for glasses with high iron content. This phenomenon is also observed during the vitrification of high-level wastes in a ceramic melter [10]. Their properties are not strongly affected at the levels 10-15 vol.…”
mentioning
confidence: 54%
“…The crystallization of the magnetitic spinels is a common phenomenon for glasses with high iron content. This phenomenon is also observed during the vitrification of high-level wastes in a ceramic melter [10]. Their properties are not strongly affected at the levels 10-15 vol.…”
mentioning
confidence: 54%
“…[24]), that indicated to potentialities of immobilization of Cs, Sr-fraction of HLW after spent nuclear fuel reprocessing; -it was established the possibility of low-temperature immobilization of waste containing volatile radionuclides (Li 9-11 for Tc and I) and contaminants; -the results obtained on hydrothermal resistance of MPP matrices according to PCT indicate low leaching rate for all components of the matrices (NR of sodium for borosilicate glass JHCM 2.7 Â 10 À2 g/(m 2 day) in Ref. [25]); -comparison of the results obtained according to standard TCLP testing with UTS limits [26] indicated that the MPP matrices are capable to fix hazardous contaminants rather strongly.…”
Section: Resultsmentioning
confidence: 99%
“… Aloy-3 tested at Khlopin Radium Institute (KRI) in an 8-h test producing 2.3 kg of glass in a 6 inch diameter CCIM operated at ~1350°C (Herman et al 2004).  ICCM-13 tested at PNNL in a 120-h test producing 51 kg of glass in a 6 inch diameter LFCM operated at 1150°C with a steady-state glass production rate of 660 kg/m 2 /d (Goles et al 2002a).…”
Section: Hanford C-106/ay-102 Formulation For Crystal Tolerant Meltersmentioning
confidence: 99%